Is The Higher Value of Green Buildings Reflected In Current Valuation Practices? - Costin Ciora; Gunther Maier; Ion Anghel (Journal of Accounting and Management Information Systems (JAMIS), 2016)
Urban sprawl and economic development brought new ways of correlating the efficiency and performance, and green buildings are spreading at higher levels. In this normative study, we discuss specific issues in how valuation methods could be considered when assessing green buildings. The real estate market is one of the most dynamic sectors, and therefore the commercial market increased in size and spreading. As the economy is growing, more office building investment created the framework for companies to operate and to further develop the economy. Our objective is to present a step-by-step approach in understanding the need of specific correlation between valuation measures and actual financial performance of this type of buildings, relative to value, rent premium, occupancy premium or even increase in productivity. With limited number of green buildings even in major cities, the issue of incorporating the premium in the final value could be challenging for the appraiser, and thus, we raise questions that could lead to further research in this area. Our analysis suggests that appraisers should take into consideration the positive effects of green buildings in their valuations. This paper is a contribution to the emerging literature on the topic of green buildings, with the focus on valuation methods.
Keywords: Q51; R30; 650; green buildings; sustainable buildings; valuation; sustainability